JumpStart your growth : a 90-day improvement plan - Maxwell, John C., 1947 (New York: Center Street, 2015)
John C. Maxwell helps readers maximize their potential with this 90-day guide that delivers daily inspiration and practical advice for bringing out your best, personally and professionally, one day at a time
Keywords: Success in business; Leadership; Business; Success; Career development